Um diálogo historiográfico: as gramáticas de língua portuguesa do séc. XVI e o Projeto de Lei 1676/1999 do séc. XX - Lima, Nelci Vieira de (2011)
This dissertation is inserted into the Portuguese Language Post Graduate Studies Programme from the Pontifícia Universidade Católica de São Paulo (PUC SP) in the History and Description of Portuguese language research thread , delimited to Linguistic Historiography, discipline in which the methods, established by their precursors Koerner (1996) and Swiggers (2009), allowed us to outline our object of study, namely, the sixteenthcentury and nineteenth-century thoughts about the use of foreign words in Portuguese. Thus, we aim to analyze and compare the first two grammars of Portuguese Language in the century. XVI, namely: João de Barros Grammar and Fernão de Oliveira one, as well as the law project 1676/1999, written by Congressman Aldo Rebelo approved in 2008. Thus, we intend to demonstrate in a comparative chart, the authors concern with borrowed words, relating their views to their contextual aspects. Besides that, Schilienben-Langue (1993, p.138) perspective, to whom what matters, is to portray the history of argumentative communities, in which it is discussed questions related to languages, endorses our course of study into such historiography thread. Taking into account the results obtained, we can say that, although our corpus of documents is composed of different genres, they are both from argumentative communities that face the same issue. Such documents represent an open room for language institutionalization, therefore being classified as linguistic policies, since they bring up human participation into the language. We can further affirm that, to both the grammarians of the sixteenth century, and to Congressman Aldo Rebelo, the twentieth century shows the same concern with borrowed words from the English language into Portuguese, both being against their use, seen t as unnecessary foreign words, as well expressing a strong nationalist feeling. This upholding in dealing with such issues sets our work within a historiography of continuity (SCHILIEBEN-LANGE, 1993, p.137). Finally, we detected that the contact between different peoples has always been a great reason for cultural exchange, including linguistic one. We also observed that, before the human kind bravely crossed the seas to establish such contacts, today, just by a simple connection with worldwide computer network, such contacts are easily established